Prevalence of Additional Canals in Maxillary First Molars in a Nigerian Population (2006)
Aim: The aim of this study was to investigate the prevalence of additional canals in maxillary first molars in a selected population in Nigeria. Methods and Materials: One hundred extracted teeth were collected from the Pedodontic and Oral Surgery clinics of the University College Hospital in Ibadan, Nigeria. The teeth were identified and their root planed to remove adherent soft tissues. Each tooth was sectioned at the cementoenamel junction (CEJ) and then again at 2 mm below the CEJ. The number of canals present in each root was noted. For the clinical aspect of the study, 30 patients with clinical and radiological evidence of pulpal involvement participated in the study. These patients had root canal therapy performed on their maxillary first molars and the number of canals was confirmed with periapical radiographs. Results: In the laboratory phase of the study 77% of the teeth sectioned had three canals while 22% had four canals with the fourth canal being a second mesiobuccal canal. Only one tooth had five canals with two canals in the palatal root, two canals in the mesiobuccal root, and the remaining canal in the distobuccal root. For the clinical phase of the study, 29 (96.7%) out of 30 patients treated had three canals while only one (3.3%) had four canals with the fourth canal being a second mesiobuccal canal. Conclusion: Clinicians should assume there are additional canals in each root when performing endodontic therapy on the maxillary first molar. Only after a thorough search for extra canals and after it is determined